The Influence of Liquidity, Capital Structure and Profitability on Company Value (Case Study of Property and Real Estate Companies Listed on the IDX 2018-2022) - Anik Rusilawati; Sri Hermuningsih; Gendro Wiyono (UNIVED Press, 2024)
This research was conducted to find out how company value (case study of property and real estate companies listed on the IDX from 2018 to 2022) can be influenced by liquidity, capital structure and profitability. We have observed 87 real estate and property companies listed on the IDX from 2018 to 2022. The dependent variable is company value and the independent variables are liquidity, capital structure and profitability. With the results of this research using a partial test (t test), there is a large and positive influence on company value produced by profitability and liquidity, and a small and positive influence produced by capital structure. This is shown by the incomplete test calculation resulting in a Beta value of 0.095 and a t count of 1.195 with a significance value of 0.146 > 0.05.